DEVELOPMENT OF STUDENT WORKSHEETS (LKPD) BASED ON SCIENCE PROCESS SKILLS AIR POLLUTION THEMES TO GROW CRITICAL THINKING ABILITY IN SMP STUDENTS - Nanda Amelia; Suroso Mukti Leksono; Vica Dian Aprelia Resti (JURNAL PENA SAINS, 2022)
Development of Student Worksheets (LKPD) Based on Science Process Skills (KPS) The theme of Air Pollution to Develop Critical Thinking Skills for Junior High School Students aims to present the results of the development and describe the feasibility level of the LKPD that has been made. The research method used is the innovative work of an item or Research and Development (RD) and the 4-D model created by Thiagarajan et al., (1974) in which there are four phases of research and development, but in this case it only concentrates on 3 stages. , especially the definition stage (Define), the planning stage (Design), and the development stage (Develop). The expert validation questionnaire instrument sheet was used to test the feasibility of a product and was evaluated by two expert lecturers and two science educators. Information dissected descriptively qualitatively and quantitatively. The results of the development of LKPD Based on Science Process Skills with the Theme of Air Pollution to Develop Critical Thinking Skills for Junior High School Students, which were viewed from the expert's assessment, scored 80.25% and were included in the proper category. Thus, the LKPD based on science process skills developed is suitable for use at the junior high school level.Keywords: Student Worksheet, Science Process Skills, Air Pollution, Critical Thinking Ability, and Junior High School.